Economic Value Added and Its Benefit for Owners and Managers of the Czech Company - Bohuslava Knapová (European Financial and Accounting Journal, 2011)
The paper is oriented to the area of management and decision making of company owners and managers. The absolute synthetic performance criterion Economic Value Added represents the criterion of the residual income and managerially measured profit. Concrete questions must be solved with the ascertainment of this financial criterion as for example how correctly to measure capital costs, how to determine the right amount of the investment capital and return on investment capital, eventually return on assets, or how to work with the time horizon in the measurement of Economic Value Added, because this criterion should be presented also as the important tool of the transformation of strategic targets on tactical time periods and to lower structural levels of investment and profitability responsibility centers. Economic Value Added should serve as one of criteria of investment decision and as criterion of the appraisal of managerial decision making, because just managers are responsible for the economical process and results of the main operating activities.
Keywords: M41; 650; Management and decision making; Performance criteria; Economic Value Added; Weighted Average Capital Costs; Owners and managers